Costing system and new way of selling in a small processing enterprise - Munzarová, Simona; Vávra, Jan; Blaháček, Daniel (SGEM, 2018)
In today's information environment, information usable for decision-making or economic development is the cornerstone of successful business. Companies build and develop managerial accounting systems as a source of information for efficient management of the company's processes. Enterprises operating in the processing industry are under strong pressure from price competition having significant impact on small companies. Moreover, the companies must continually adapt to a changing environment and come up with innovations of a different nature like product innovation, services, management procedures innovations or, for example, finding new ways of selling. In such situations, it is necessary to know the cost of products or processes. This can be obtained from a carefully and precisely developed costing system, which can be the basis for price decision making, resources allocation and determination of long-term business direction. This paper describes the results of analyzes and evaluation of the cost management and costing systems in the practice of a process manufacturing enterprise, including recommendations for changes to this system. The paper also deals with the integration of managerial accounting into supply chain management. Advantages and disadvantages of a selected new way of selling products are discussed and possibilities of the cost management system application in searching new ways of selling are evaluated.
Systém kalkulací nákladů a nový způsob prodeje v malé zpracovatelské firmě
Keywords: Costing system; managerial accounting; supply chain; online auction; Kalkulační systém; manažerské účetnictví; dodavatelský řetězec; online aukce